Bioactive Compounds, Antioxidant Capacity, and Fatty Acids in Different Parts of Four Unexplored Fruits - Adriela Albino Rydlewski; Damila Rodrigues de Morais; Eliza Mariane Rotta; Thiago Claus; Julianna Matias Vagula; Michele Cristina da Silva; Oscar Oliveira Santos Junior; Jesuí Vergílio Visentainer (Journal of Food Quality)
Total phenolic content (TPC), total flavonoids (TF), total anthocyanins (TA), and antioxidant capacity of different parts of four unexplored fruits from Brazil (Syzygium cumini Lam, Solanum nigrum Linn, Inga edulis Mart, and Hovenia dulcis Thunb) were determined; the bioactive compounds and fatty acids were quantified and identified by high-performance liquid chromatography and gas chromatography, respectively. S. cumini peels contained the most TA (63.31 mg/100 g), whilst H. dulcis pulp and peels had the highest TPC (518.18 mg GAE/100 g) and TF (76.54 mg EQ/g). Phenolic compounds responsible for antioxidant capacity of fruits were gallic acid, ellagic acid, kaempferol, and epicatechin. H. dulcis seed showed the highest level of the essential fatty acid omega-3 (3985.95 mg/100 g). PCA showed that PC1 and PC2 explained 90.43% of the total variability of the antioxidant data. Most of the seeds showed omega-3, omega-6, and omega-9 fatty acids at significant concentrations, with two PCs explaining 93.80% of the total variance of the fatty acid contents.